Orexin receptor 2 agonist activates diaphragm and genioglossus muscle through stimulating inspiratory neurons in the pre-Bötzinger complex, and phrenic and hypoglossal motoneurons in rodents. - Ryuji Yamada; Tatsuki Koike; Masanori Nakakariya; Haruhide Kimura (PLoS ONE, 2024)
Orexin-mediated stimulation of orexin receptors 1/2 (OX[1/2]R) may stimulate the diaphragm and genioglossus muscle via activation of inspiratory neurons in the pre-Bötzinger complex, which are critical for the generation of inspiratory rhythm, and phrenic and hypoglossal motoneurons. Herein, we assessed the effects of OX2R-selective agonists TAK-925 (danavorexton) and OX-201 on respiratory function. In in vitro electrophysiologic analyses using rat medullary slices, danavorexton and OX-201 showed tendency and significant effect, respectively, in increasing the frequency of inspiratory synaptic currents of inspiratory neurons in the pre-Bötzinger complex. In rat medullary slices, both danavorexton and OX-201 significantly increased the frequency of inspiratory synaptic currents of hypoglossal motoneurons. Danavorexton and OX-201 also showed significant effect and tendency, respectively, in increasing the frequency of burst activity recorded from the cervical (C3-C5) ventral root, which contains axons of phrenic motoneurons, in in vitro electrophysiologic analyses from rat isolated brainstem-spinal cord preparations. Electromyogram recordings revealed that intravenous administration of OX-201 increased burst frequency of the diaphragm and burst amplitude of the genioglossus muscle in isoflurane- and urethane-anesthetized rats, respectively. In whole-body plethysmography analyses, oral administration of OX-201 increased respiratory activity in free-moving mice. Overall, these results suggest that OX2R-selective agonists enhance respiratory function via activation of the diaphragm and genioglossus muscle through stimulation of inspiratory neurons in the pre-Bötzinger complex, and phrenic and hypoglossal motoneurons. OX2R-selective agonists could be promising drugs for various conditions with respiratory dysfunction.